Using a general classification scheme and domain thesauri to build an organizational taxonomy for supporting navigation. - Wang, Zhonghong. (2010)
Taxonomies are increasingly being chosen as knowledge organization systems to organize content within organizations and support navigation of web sites or digital repositories. They are becoming an essential component of knowledge management strategies within organizations. Researchers have recommended using classification schemes and thesauri as sources for building organizational taxonomies in order to leverage on terms, term relationships, and structures of these sophisticated systems and reduce the taxonomy construction effort. The purpose of the study was to examine how a general classification scheme and domain thesauri can be used as sources in the construction of an organizational taxonomy used for navigation of an organizational repository. In particular, the study sought to find out what support they provide in the construction of the hierarchical structure and categories of the taxonomy and steps to take in the construction process.